Therapeutic potential of a pyridoxal‐based vanadium(IV) complex showing selective cytotoxicity for cancer versus healthy cells. Issue 11 (25th July 2013) - Strianese, Maria; Basile, Anna; Mazzone, Antonio; Morello, Silvana; Turco, Maria Caterina; Pellecchia, Claudio
Abstract Vanadium compounds can exert anticancer effects, partly due to inhibition of tyrosine phosphatases. Here, we report the effect of N, N′‐ethylenebis (pyridoxylideneiminato) vanadium (IV) complex (Pyr2enV(IV)), that induced 93% and 57% of cell mortality in A375 (human melanoma) and A549 (human lung carcinoma) cells, respectively; the mortality was <24% in other cancer cell lines and in human normal epidermal keratinocytes, lung cells and peripheral blood mononuclear cells. The mechanism of Pyr2enV(IV) effect relied on apoptosis induction; this was triggered by ROS increase, followed by mitochondrial membrane depolarization. Indeed, the addition of N‐acetyl cysteine to cell cultures abated Pyr2enV(IV)‐induced apoptosis. These results disclose the pro‐apoptotic activity of Pyr2enV(IV) and its mechanism, relying on intracellular ROS increase. J. Cell. Physiol. 228: 2202–2209, 2013. © 2013 Wiley Periodicals, Inc.